2013
DOI: 10.1115/1.4024825
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Virtual Functional Prototyping Process for the Rapid Manufacture of Passive-Dynamic Ankle-Foot Orthoses

Abstract: Passive-dynamic ankle-foot orthosis (PD-AFO) bending stiffness is a key functional characteristic for achieving enhanced gait function. However, current orthosis customization methods inhibit objective premanufacture tuning of the PD-AFO bending stiffness, making optimization of orthosis function challenging. We have developed a novel virtual functional prototyping (VFP) process, which harnesses the strengths of computer aided design (CAD) model parameterization and finite element analysis, to quantitatively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 30 publications
3
77
0
Order By: Relevance
“…9 Examples of AM AFOs, produced by: (a) Faustini et al [21], (b) Mavroidis et al [22], (c) Schrank et al [23], (d) Telfer et al [17], (e) Creylman et al [24], (f) Schrank et al [25], (g) Chen et al [26], and (h) Harper et al [27].…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Examples of AM AFOs, produced by: (a) Faustini et al [21], (b) Mavroidis et al [22], (c) Schrank et al [23], (d) Telfer et al [17], (e) Creylman et al [24], (f) Schrank et al [25], (g) Chen et al [26], and (h) Harper et al [27].…”
Section: Other Applicationsmentioning
confidence: 99%
“…9(e)) on eight subjects with unilateral drop foot gait, evaluated gait performance and concluded that SLS AFOs had at least equivalent performances as conventional AFOs. Schrank et al [25] integrated the CAD model parameterization and FEM analysis to quantitatively tune, predict and experimentally validate the bending stiffness of AFOs made by FDM. AFOs with different stiffness levels were fabricated ( Fig.…”
Section: Traditional and Additive Manufacturing Of The Foot Orthosismentioning
confidence: 99%
“…In the field of prosthetics and orthotics, FEA has been used to evaluate and design a variety of devices [1013]. FEA can also predict stress distribution and material deformation patterns [5–6,8,14] and can determine the orthosis dimensions needed to mimic design characteristics of commercial orthoses [15]. FEA of fully parameterized CAD models may hold great potential for rapidly identifying optimal PLS AFO functional characteristics, such as bending stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) printing, one of the most recent forms of CAM, has proven efficacy in the fabrication of ankle foot orthoses (AFO) with reports of excellent dimensional accuracy, good manufacturing precision, and performance that is at least equivalent to hand-crafted AFO’s [7-9]. Recent studies report positive subjective comfort ratings and similar biomechanical gait parameters with the use of orthoses manufactured using 3D printing in comparison to orthoses fabricated using traditional means [1,6,10].…”
Section: Resultsmentioning
confidence: 99%